Control of Cell Proliferation: Is the Default State of Cells Quiescence or Proliferation? - Sonnenschein, Carlos; Soto, Ana M (Organisms. Journal of Biological Sciences, 2021)
The control of cell proliferation in multicellular organisms remains a perennially controversial subject in experimental biology. In this essay, we examine the historical background and the rationale adopted by diverse theoretical and experimental research programs aimed at explaining how and why cells proliferate. We examine the premises that favor the notion that cells in multicellular organisms require direct stimulation from the outside (a task attributed to alleged growth factors) or from the inside (through the elusive action of oncogenes). Our analysis suggests that neither growth factors nor oncogenes directly stimulate the proliferation of cells. Based on evolutionary precedents, theoretical considerations and empirical data we posit instead that proliferation is the default state of all cells; thus, a search for extra- and intra-cellular inhibitory constraints promises to be productive when explaining this basic property of cells within the context of normal and abnormal developmental biology.